Scottish highlands and the Atlantic world social networks and identities - Kehoe, S. Karly ca. 20./21. Jh; Dalglish, Chris; Tindley, Annie ca. 20./21. Jh (Edinburgh University Press, 2023)
Reveals the importance of social networks and identities to defining Highland Scots' engagements with Empire and its lasting legaciesA central, reliable and readable reference point for study of a topic that will interest a wide range of scholars and the reading public internationally Individual chapters that will suit individual specialisms, while still being accessible to readers from other disciplines/professionsInnovative and topical commentaries which are highly readable, provocative and agenda-settingImportant (re)considerations of neglected and/or understudied perspectives and areas of scholarship,
Keywords: Scottish Studies; HISTORY / Europe / Great Britain / General; Scots -- Great Britain -- Colonies -- History; Scots -- Great Britain -- History